2021
DOI: 10.15678/eber.2021.090306
|View full text |Cite
|
Sign up to set email alerts
|

Identity crisis of artists during the Covid-19 pandemic and shift towards entrepreneurship

Abstract: The objective of the article is to understand the changes in artists' identity facing the global obstacle caused by the Covid-19 pandemic and the impact of the identity crisis into the shift towards entrepreneurial behaviours. Creative individuals seems to be perfect examples of adjustments to the changing environment. Research Design & Methods:The qualitative research was conducted in form of in-depth interviews with key informants (artists with different entrepreneurial experiences from different countries a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 78 publications
0
26
0
Order By: Relevance
“…Given the substantial reduction in work for the majority of professionals working in the performing arts field, it is unsurprising that many also reported that the pandemic had a profound financial impact [19,20,21,22,23,24]. In several studies, over 70% of participants reported income reductions [19,21,24; over half (54%) of Spiro et al's [19] 385 participants considered themselves to be in financial hardship whilst almost half (43.9%) of Teixeira et al's [24] 174 participants were earning minimum wage or less.…”
Section: Loss Of Incomementioning
confidence: 99%
“…Given the substantial reduction in work for the majority of professionals working in the performing arts field, it is unsurprising that many also reported that the pandemic had a profound financial impact [19,20,21,22,23,24]. In several studies, over 70% of participants reported income reductions [19,21,24; over half (54%) of Spiro et al's [19] 385 participants considered themselves to be in financial hardship whilst almost half (43.9%) of Teixeira et al's [24] 174 participants were earning minimum wage or less.…”
Section: Loss Of Incomementioning
confidence: 99%
“…This philosophy was the initial point for this research. Investigation the creative identities of a creator, artist, manager, entrepreneur, and leader in one research because these identities are driving forces of development and usually occur not alone, being combined in pairs or larger groups: e.g., manager-entrepreneur, artist-leader, creator-artist-manager (Szostak and Sułkowski, 2021a;2021c). Those complex identities may bring problems, dilemmas, and tensions (Mochalova, 2020;Warhurst and Black, 2017) but also may reveal new dimensions, skills, and possibilities for individuals if they can manage the particular identities by identity regulation, identity work, paradoxical thinking or creativity development (Antal et al, 2016;Szostak and Sułkowski, 2021b).…”
Section: Introductionmentioning
confidence: 99%
“…Perception of the creative identities by society is not evident, especially that these identities occur mostly merged in twosomes, like artist-entrepreneur (Bass, 2017;Szostak and Sułkowski, 2021b), artist-leader, artist-manager, manager-entrepreneur (Szostak and Sułkowski, 2020a;2021d), or threesomes, like creator-artist-manager or artist-manager-entrepreneur (Szostak and Sułkowski, 2021b). Individuals with complex identities feel dilemmas, internal difficulties, and identity tensions (Hay, 2014;Mochalova, 2020).…”
Section: Introduction and Theoretical Backgroundmentioning
confidence: 99%